Vitamin A Affects Flatfish Development in a Thyroid Hormone Signaling and Metamorphic Stage Dependent Manner - Fernández, Ignacio; Ortiz-Delgado, Juan B.; Darias, Maria J.; Hontoria, Francisco; Andree, Karl B.; Manchado, Manuel; Sarasquete, Carmen; Gisbert, Enric (Frontiers in Physiology, 2017)
Vitamin A (VA) and retinoid derivatives are known morphogens controlling vertebrate development. Despite the research effort conducted during the last decade, the precise mechanism of how VA induces post-natal bone changes, and particularly those operating through crosstalk with the thyroid hormones (THs) remain to be fully understood. Since effects and mechanisms seem to be dose and time-dependent, flatfish are an interesting study model as they undergo a characteristic process of metamorphosis driven by THs that can be followed by external appearance. Here, we studied the effects of VA imbalance that might determine Senegalese sole (Solea senegalensis) skeletogenetic phenotype through development of thyroid follicles, THs homeostasis and signaling when a dietary VA excess was specifically provided during pre-, pro- or post-metamorphic stages using enriched rotifers and Artemia as carriers. The increased VA content in enriched live prey was associated to a higher VA content in fish at all developmental stages. Dietary VA content clearly affected thyroid follicle development, T3 and T4 immunoreactive staining, skeletogenesis and mineralization in a dose and time-dependent fashion. Gene expression analysis showed that VA levels modified the mRNA abundance of VA- and TH-specific nuclear receptors at specific developmental stages. Present results provide new and key knowledge to better understand how VA and TH pathways interact at tissue, cellular and nuclear level at different developmental periods in Senegalese sole, unveiling how dietary modulation might determine juvenile phenotype and physiology.